Social Workers’ Orientation Toward the Evidence-Based Practice Process: A Dutch Survey - van der Zwet, Renske J. M. (Res Soc Work Pract, 2014)
OBJECTIVES: This study assesses social workers’ orientation toward the evidence-based practice (EBP) process and explores which specific variables (e.g. age) are associated. METHODS: Data were collected from 341 Dutch social workers through an online survey which included a Dutch translation of the EBP Process Assessment Scale (EBPPAS), along with 13 background/demographic questions. RESULTS: The overall level of orientation toward the EBP process is relatively low. Although respondents are slightly familiar with it and have slightly positive attitudes about it, their intentions to engage in it and their actual engagement are relatively low. Respondents who followed a course on the EBP process as a student are more oriented toward it than those who did not. Social workers under 29 are more familiar with the EBP process than those over 29. CONCLUSIONS: We recommend educators to take a more active role in teaching the EBP process to students and social workers.